The impression management benefits of humorous self-disclosures: How humor influences perceptions of veracity - Bitterly, T. Bradford; Schweitzer, Maurice E. (Organizational behavior and human decision processes, 2019)
•Humor reduces the perceived veracity of proximal statements.•Humor diminishes the perceived veracity of negative disclosures.•Adding humor to negative disclosures boosts perceptions of warmth and competence.•Humor is a powerful impression management tool. Across five studies, we identify humor as a powerful impression management tool that influences perceptions of veracity. In many domains, such as negotiations and interviews, individuals face a challenge with respect to disclosing negative information and managing impressions. For example, an interviewer may ask an applicant to name their greatest weakness. In these settings, disclosures that reveal negative information (e.g., “I am not good at math.”) can harm perceptions of warmth and competence. We demonstrate that pairing a humorous statement with a disclosure (e.g., “I am not good at math. Geometry is where I draw the line.”) changes perceptions of the veracity of the disclosure; disclosures are less likely to be judged as true when they are accompanied by a humorous statement than when they are not. We introduce the Speaker's Inferred Motive (SIM) Model and consider the possibility that (a) speakers pursue different motives, such as a transmission-of-ideas motive (to convey information) or an entertainment motive (to amuse an audience), (b) audience members infer the speaker’s motive, and (c) these inferences influence perceptions of the veracity of proximal disclosures. As a result, by using humor, a speaker may signal a shift in motive and diminish perceptions of the veracity of both the humorous statement and proximal claims. Taken together, when a target discloses negative information, including information that is highly relevant to the conversational partner, the use of humor can boost perceptions of warmth and competence. We discuss implications of our findings with respect to communication, interpersonal perception, and impression management.